2015
DOI: 10.1186/s12889-015-2345-6
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the magnitude, barriers, and outcomes of HIV status disclosure among women participating in a perinatal HIV transmission study, “the Nevirapine Repeat Pregnancy study”

Abstract: BackgroundHIV status disclosure is a difficult emotional task for HIV-infected persons and may create the opportunity for both social support and rejection. In this study, we evaluated the proportions, patterns, barriers and outcomes of HIV- 1 status disclosure among a group of women in Uganda.MethodsAn exit interview was conducted one year post-partum for 85 HIV-infected women who participated in a study of HIV-1 transmission rates among NVP-experienced compared with NVP-naïve women in “The Nevirapine Repeat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Encouragingly, the study also revealed a high overall disclosure rate (90%) when considering those who disclosed to at least one person, including a sexual partner or someone else. This aligns with findings from other studies by [13,14]. The high disclosure rates observed in the God is Good Support Group suggest a potential link between support group membership and increased disclosure.…”
Section: Discussionsupporting
confidence: 90%
“…Encouragingly, the study also revealed a high overall disclosure rate (90%) when considering those who disclosed to at least one person, including a sexual partner or someone else. This aligns with findings from other studies by [13,14]. The high disclosure rates observed in the God is Good Support Group suggest a potential link between support group membership and increased disclosure.…”
Section: Discussionsupporting
confidence: 90%
“…Lack of disclosure of HIV positive status has been associated with increased LTFU [ 23 , 41 ] in women enrolled in PMTCT programs. We hypothesize that women who have not disclosed report to their partners that they visit monthly a health care facility for ANC, but not for HIV care; after delivering they may stop coming to the clinic since they cannot justify to their partners' monthly visits to a health care facility.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study found out that the rate of disclosure to at least one person (including a sexual partner or anyone else) was high (94.1%). Other studies also found similar or higher rates of disclosure to at least one person [ 37 , 38 ]. Among those who disclosed to at least one person, nearly half of them (49.3%) only disclosed to their sexual partners and only 8.1% disclosed to two or more people apart from their sexual partners.…”
Section: Discussionmentioning
confidence: 61%